Sport development and sport for development in the caribbean : a sociology of emerging trends - McCree, Roy (Research in the sociology of sport ;, 2025)
The emergence of sport for development as a developmental strategy led by the United Nations and the use of sport by companies around the world as part of their Corporate Social Responsibility strategies have brought to the fore its developmental utility. Within this broader global context, Sport Development and Sport for Development in the Caribbean offers a unique focus on the Caribbean context to examine issues related to sport development and sport for development across a range of Caribbean countries that include Cuba, the Dominican Republic, Haiti, Jamaica, Martinique, and Trinidad and Tobago. Building on a relatively small, emerging body of work on the Caribbean context, the chapters showcase how this region has been an important part of the processes of globalization, commercialization and professionalization that have expressed themselves in and through sport. Touching on a range of sports which have formed part of Caribbean sport history and culture, including cricket, athletics, baseball and soccer, authors examine a broad array of issues in Caribbean sport that have come to define the contemporary scope of sport sociology. Topics covered are globalization, commercialization, professionalization, nationalism, gender, race, national identity, nationalism, athletic migration and disability.